Vortex Assisted Extraction for Propylparaben Analysis in Cosmetics - Noorashikin Md Saleh (ASM Science Journal, 2019)
Propylparaben is an ester of para-hydroxybenzoic acid and commonly used as a preservative in the cosmetics, pharmaceuticals and food products. However, several recent reports demonstrated that paraben possesses an estrogenic activity and causes cancer for the consumer. Therefore, the extraction of propylparaben from cosmetics requires method that is easy, fast, user-friendly and accurate reproducible result. Conventional techniques such as liquid-liquid extraction (LLE) show some disadvantages such as the use of a large amount of solvent and time-consuming. Therefore, this present study aims to apply vortex assisted extraction (VAE) in determining the concentration of propylparaben in cosmetic samples and analyse using ultraviolet spectroscopy (UV-Vis). From the results, the calibration curve was found in the range of 0.2-1.0mg/L with a regression coefficient, r2=0.9932 and relative standard deviation (RSD) less than 1%. The limit of detection (LOD) and quantification (LOQ) for VAE was 0.090mg/L and 0.302mg/L, respectively. Operating parameters for VAE (concentration of salt, type of solvent and extraction time) and LLE (concentration of salt, extraction time, type and volume of solvent) have been optimised and subsequently applied to the extraction using the real samples. Ten cosmetic products were chosen randomly such as shampoo, body wash, gargle, toner, mouth rinse, lotion, feminine wash, face mask, and scrub. The recoveries for VAE and LLE were 76.7% -103.4% (RSD=0.1-4.0%) and 62.5%-93.9% (RSD=<1%), respectively. Therefore, VAE is the best modern method for determination of propylparaben in cosmetics because it is simpler, faster with high percentage of recovery compared to other techniques.